Chris Baker y Pasuk Phongpaichit (trads. y eds.), The Tale of Khun Chang Khun Phaen, Chiang Mai, Silkworm Books, 2010, 970 pp. - Francisco Javier Haro (El Colegio de México, A.C., 2015)
Chris Baker y Pasuk Phongpaichit (trads. y eds.), The Tale of Khun Chang Khun Phaen, Chiang Mai, Silkworm Books, 2010, 970 pp.